School lunch adequacy, daily nutrient intake, and nutritional status among schoolchildren in a double burden setting - Mamat Rahmat; Nitta Isdiany; Agustina Indri Hapsari (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Nutritional problems among school-aged children in Indonesia remain characterized by stunting alongside increasing overweight and obesity.School lunch programs are expected to support children’s nutrient intake, but their relationship with nutritional status remains unclear. Objective: To analyze the correlation between school lunch nutrient adequacy, daily nutrient intake, and the nutritional status of elementary school students. Methods: An analytical observational study with a cross-sectional design was conducted among 44 students in grades 4–6 at SD Plus Nurul Aulia, Cimahi City, in September 2025. Data were collected through interviews, 2×24-hour food recall to assess daily intake, two-day food weighing to assess school lunch intake, and anthropometric measurements. Nutritional status was assessed using height-for-age (HAZ) and body mass index-for-age (BAZ).Correlation analysis was performed using Pearson or Spearman tests according to data distribution. Results: The prevalence of stunting was 9.09%, while overweight and obesity reached 36.36%.The mean adequacy of daily intake relative to the recommended dietary allowance (RDA) was 90.68% for energy, 122.42% for protein, 79.73% for fat, 88.30% for carbohydrates, and 143.63% for iron. The mean adequacy of school lunch relative to daily RDA was 83.28% for energy, 109.16% for protein, 62.89% for fat, 86.11% for carbohydrates, and 109.33% for iron. No significant correlation was found between daily intake or school lunch intake and HAZ or BAZ (p>0.05). The highest correlations for daily intake with HAZ were observed for iron (r=0.269;p=0.077) and energy (r=0.234; p=0.127). Conclusion: Neither school lunch nutrient adequacy nor daily nutrient intake was significantly correlated with students’ nutritional status.